Outcomes of Percutaneous Drainage vs. Antibiotic Therapy Alone or Emergency Surgery in Periappendiceal Abscess - Walailak Chaiyasoot (Siriraj Medical Journal, 2020)
Objective: To compare the treatment outcomes in patients with periappendiceal abscess who underwent percutaneous drainage, antibiotics therapy alone, or emergency surgery in a single hospital. Methods: From January, 2013 to December, 2018, a retrospective cohort study was done in 124 patients who were diagnosed as periappendiceal abscess or phlegmon by CT scan in Siriraj Hospital, Bangkok. We evaluated patients’ demographics, the abscess characteristics, and the outcomes of treatment which including one of the three therapeutic options: image-guided percutaneous drainage, antibiotics alone, or emergency surgery. Results: Among 124 patients, 44 (35.5%) underwent percutaneous drainage, 57 (46.0%) were treated with antibiotics alone, and 23 (18.5%) underwent emergency surgery. The percentages of patients with successful outcomes were 84.1% in percutaneous drainage, 98.2% in antibiotics treatment alone, and 95.7% in surgery. Antibiotics treatment alone was significantly associated with more successful outcome, with odds ratio (OR) of 9.882 (95% CI 1.162-84.066; P value 0.036), as compared with percutaneous drainage, while surgery showed no significant difference. The length of stay in the percutaneous drainage group (median of 10 days, minimum or maximum of 3 or 67 days) was significantly longer than the antibiotics group (median of 6 days, minimum or maximum of 1 and 53 days) with a P value of 0.008. Conclusion: The antibiotics treatment alone was significantly associated with more successful outcomes and shorter hospital stays as compared with percutaneous drainage in patients with a periappendiceal abscess or a phlegmon. Percutaneous drainage should be used for patients who show no improvement after antibiotics treatment.